2016
DOI: 10.1111/ced.12915
|View full text |Cite
|
Sign up to set email alerts
|

A new method for evaluation of the autonomic nervous system in patients with idiopathic hyperhidrosis: systolic blood pressure and heart rate recovery after graded exercise

Abstract: The significantly impaired SBPR and decreased HRR values we observed in patients with IH may indicate that the autonomic dysfunction in IH is a systemic disorder with cardiovascular effects, rather than a merely local disease. Both HRR and SBPR values may provide additional information about predicting adverse cardiovascular events in the future even in apparently healthy young patients with IH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
0
8
1
Order By: Relevance
“…In our preliminary analysis, the HRR profiles of 25 patients with known IH and 25 HCs with no known autonomic dysfunction were assessed. In contrast to the results of Alihanoglu et al ., we found that the HRR indices were similar in patients with IH and the HCs. However, we found that the hyperbolic‐type first‐minute exercise HRR curve was more common in patients with IH than in HCs (67% vs. 28%, P = 0.02).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In our preliminary analysis, the HRR profiles of 25 patients with known IH and 25 HCs with no known autonomic dysfunction were assessed. In contrast to the results of Alihanoglu et al ., we found that the HRR indices were similar in patients with IH and the HCs. However, we found that the hyperbolic‐type first‐minute exercise HRR curve was more common in patients with IH than in HCs (67% vs. 28%, P = 0.02).…”
contrasting
confidence: 99%
“…We read with great interest the paper by Alihanoglu et al . published recently in Clinical and Experimental Dermatology .…”
mentioning
confidence: 97%
“…The objective of the present study was to investigate the autonomic behavior in patients diagnosed with different types of PFHH using HRV analysis in the domains of time, frequency, and nonlinearity in relation to an apparently healthy control group. Our results allowed us to conclude that although PFHH presents a basis for some autonomic dysfunction, this will necessarily or predominantly occur at the "peripheral" level, that is, in the sweat glands or in their vicinity and will not be related to HRV [15,20,21,25,39,40].…”
Section: Discussionmentioning
confidence: 74%
“…Sweat gland disorders can of-ten result in changes in sweat secretion and release of sweat to the skin surface. Current detailed studies on the cellular mechanisms involved in sweat secretion bring evidence that there are differences in the proteins that control the influx of calcium (Ca +2 ) to the interior of the cell between hyperhidrotic and control cells [39,40]. These findings suggest that changes in the intracellular mechanisms of sweat secretion may be involved in excessive sweating in HH.…”
Section: Discussionmentioning
confidence: 99%
“…The bidirectional changes in HRR over increasing and decreasing physical activity may be used to follow a physical activity intervention in RA to identify non-responder and non-adherent participants with potential hypertension risk, despite normal resting blood pressure and normal exercise ECG findings. From a practical standpoint, exercising ECG and extending it for only several minutes into exercise recovery provides a unique, minimally invasive means to assess HR and blood pressure responses to exercise to indirectly determine participant's response or adherence to physical activity and to predict the CVD risk ( 28 , 50 ), and also mainly to detect hypertension early ( 39 , 42 , 51 ). It was already reported in the literature that a delayed SBP decrease post-exercise was more accurate than ST segment depression for the diagnosis of coronary artery disease (CAD) ( 39 , 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%